Shanghai splendor : economic sentiments and the making of modern China, 1843-1949 - Yeh, Wen-Hsin (University of California Press, 2007)
Rich with details of everyday life, this multifaceted social and cultural history of China's leading metropolis in the 20th century offers a kaleidoscopic view of Shanghai as the major site of Chinese modernisation.